Pengembangan Kawasan Wisata Pantai Lamangkia Desa Topejawa, Kecamatan Mangarabombang, Kabupaten Takalar - M. Nurhidayat; Shirly Wunas; Suriana La Tanrang (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2015)
The tourism sector in Indonesia has recently progressed. The tourism sector has experienced a significant increase in this decade, placing it as the third largest foreign exchange earner in Indonesia. Lamangkia Beach is one of the beach tourism in Takalar Regency that has not been developed by the Takalar Regency Government. The purpose of this research is to identify the tourism potential, analyze the social activities of the community in accordance with tourism activities, and develop development concepts that can be applied in the Lamangkia Coastal Region. The method of data collection is done through observation, interviews, and literature studies. The analytical method used is qualitative descriptive analysis and concept analysis with an idealist and functionalist approach. The results showed that the potential of Lamangkia Beach in the form of water, views, types of sand, and tourist objects and attractions. The social potential of the community in the form of community activities (fishing and making nets), interactions between individuals, community crafts (woven mats and making nets), and the implementation of traditional events. Development concepts that can be applied include: conservation, community empowerment, structuring tourist objects and attractions, providing infrastructure, accessibility, spatial planning for tourism areas, and promotion and marketing.